Working at the boundaries: Middle managerial work as a source of emancipation and alienation - Azambuja, Ricardo; Islam, Gazi (Human relations (New York), 2019)
The current article examines the experience of middle management through the concept of boundary work, characterized as the work of negotiating between multiple roles in the interstices of organizational groups. Through an ethnographic study of a Brazilian accounting firm, we explore the ambivalent experience of boundary work as characteristic of professional middle managerial workers. Our managers described themselves as proactive and reflexive agents, on the one hand, yet also as lacking autonomy and a sense of belonging, on the other. We examine this tension as a contrast between forces of emancipation (i.e. sense of mastery, autonomy, empowerment and reflexivity) and alienation (i.e. fatigue, lack of self-determination, and detachment from their profession and coworkers). We discuss these forces and their implications for managerial work in the light that, in our findings, managers routinely shift between being agential and reflexive mediators (boundary subjects) and interfacing and coordination devices (boundary objects).